LIFE CYCLE ASSESSMENT PERKERASAN JALAN BERASPAL DENGAN RECLAIMED ASPHALT PAVEMENT DI RUAS JALAN NASIONAL PROVINSI JAWA BARAT - Dwi Ajeng Sarasputri (Jurnal Jalan-Jembatan, 2022)
In order to achieve sustainable development and offset the high demand for improving the quality of roads as one of the socio-economic infrastructures, an optimal strategy is required. The use of Reclaimed Asphalt Pavement (RAP) has been developed as an effort to minimize aggregate waste due to asphalt pavement production. This study aims to estimate the cradle to gate asphalt road life cycle impact through Life Cycle Assessment (LCA) with OpenLCA software and Recipe 2016 Midpoint (H) method, to compare the impact between asphalt with natural aggregate and asphalt contain 50% RAP, and to analyze the components of activities that contribute the most to the impact. The case study is rehabilitation project of national asphalt roads in West Java Province with 1 km asphalt road functional unit. The result shows that the use of 50% RAP levels can reduce the impact of global warming (GWP) of 1,05 ton CO2 eq, fossil resource scarcity (FRS) of 19,60 ton oil eq, human carcinogenic toxicity (HCT) of 0,25 ton 1,4-DCB, and human non-carcinogenic toxicity (HnCT) of 1,79 ton 1,4-DCB compared to asphalt without RAP, while the impact of fine particle formation on asphalt with 50% RAP is 0,02 ton PM2,5 eq higher than asphalt without RAP. Diesel is the main activity that contributes the largest emissions to most impacts, and fuel efficiency efforts can reduce the overall impact.